EFL Students’ Perception of Speaking Course through Debating Process during the Pandemic - Sri Ayu Indah Lestari; Yousef Bani Ahmad; Sumarta Sumarta (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
Speaking is one of four crucial skills in English language learning. The pupils communicate and share their thoughts by language in their everyday life. They use language to make an order, to communicate with others, to express their emotions, thoughts and ideas. Speaking is one of the subjects in an English Education Department, the researcher inspired to evaluate whether the debating method increase the student’s speaking skill or not, especially during the outbreak of the corona virus. As the impact of this virus matter, education is one of some fields got impacted, so schools and universities are closed for more than a year. The new way of teaching learning could be a challenge for both students and instructors. Moreover, there is a need to know on how the students’ perception toward the teaching learning process via video conference, was it feel the same. However, this paper investigates the EFL students’ perception of speaking courses through the debating process during the pandemic. This study employing qualitative narrative inquiry. The data gathered from some the experiences of three Indonesian EFL students in university. The author was done collected the data conducted a semi-structured interview using a call through messages application. The study found that the participants’ perceptions toward speaking course conducted via video conference encourage their critical thinking, their team-work, students’ social skill and their interest towards the subject. It seems that the debate technique is impacted the students positively by promoting their critical thinking, social skill, team work and students’ satisfaction towards the subject.